2017
DOI: 10.1063/1.4989774
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles physicochemically bonded onto tungsten disulfide nanosheet edges exhibit augmented plasmon damping

Abstract: Augmented plasmonic damping of dipole-resonant gold (Au) nanoparticles (NP) physicochemically bonded onto edges of tungsten disulfide (WS2) nanosheets, ostensibly due to hot electron injection, is quantified using electron energy loss spectroscopy (EELS). EELS allows single-particle spatial resolution. A measured 0.23 eV bandwidth expansion of the localized surface plasmon resonance upon covalent bonding of 20 nm AuNP to WS2 edges was deemed significant by Welch’s t-test. Approximately 0.19 eV of the measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Darkfield scanning TEM coincident with electron energy loss spectroscopy performed in parallel with the current work elucidated plasmon damping at the physiochemical WS 2 -Au bond, providing an important first step in understanding energy transfer and edge states in this hybrid material. 44 XPS still shows evidence of a covalent Au-S bond in the purified samples (SI section 7.3). For the purified l-WS 2 -Au1 sample, some of the 10-20 nm diameter AuNPs are still present (wide-view image Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Darkfield scanning TEM coincident with electron energy loss spectroscopy performed in parallel with the current work elucidated plasmon damping at the physiochemical WS 2 -Au bond, providing an important first step in understanding energy transfer and edge states in this hybrid material. 44 XPS still shows evidence of a covalent Au-S bond in the purified samples (SI section 7.3). For the purified l-WS 2 -Au1 sample, some of the 10-20 nm diameter AuNPs are still present (wide-view image Fig.…”
Section: Resultsmentioning
confidence: 93%
“…[85] As reported by Forcherio et al, [86] hot electrons generatedi np lasmonic gold nanoparticles deposited onto WS 2 readily transfer to the disulfide counterpart in 7f s, with aq uantum efficiency of up to 11 AE 5%.F ormation of ad irect chemicalb ond between gold and an outer sulfur layer of WS 2 plays ab eneficial role in this process, resulting in faster and more efficient hot electron transfer,a sc ompared to AuNPs physically deposited onto MoS 2 nanoflakes. [86,87] Note that our study revealed possible AuÀSb ondingo nt he AuNP/NT-WS 2 interface of the prepared nanocomposites. We suggest that the transfer of hot electrons additionally increases the "light" conductance of Au-NT-WS 2 nanocomposite resulting in the enhanced photoresponse.…”
Section: Nt-wsmentioning
confidence: 74%
“…Typically, the excited plasmon in AuNPs has multiple effects on the semiconductor part of the nanocomposite, including energy and charge carrier transfer, amplification of local electrical fields and plasmon‐induced local heating . As reported by Forcherio et al., hot electrons generated in plasmonic gold nanoparticles deposited onto WS 2 readily transfer to the disulfide counterpart in 7 fs, with a quantum efficiency of up to 11±5 %. Formation of a direct chemical bond between gold and an outer sulfur layer of WS 2 plays a beneficial role in this process, resulting in faster and more efficient hot electron transfer, as compared to AuNPs physically deposited onto MoS 2 nanoflakes .…”
Section: Resultsmentioning
confidence: 99%
“…An 11±5% quantum efficiency of HET from ca. 20 nm AuNPs reduced on WS 2 nanosheets was estimated by comparing electron energy loss spectroscopy (EELS) measured and DDA simulation [22].…”
Section: Enhanced Catalysis By Optical Nanoantenna Reduced On Transitmentioning
confidence: 99%